The Role of Play in Early Childhood Education for Developing Creative Problem-Solving Skills: A Longitudinal Study - Sisilia Prima Yanuaria Buka; Bruna Costa; Pedro Silva; Saiful Fallah (Yayasan Adra Karima Hubbi, 2025)
Play is increasingly recognized as a crucial foundation for fostering creativity and problem-solving abilities in early childhood education. In a rapidly changing world that demands flexible thinking and innovation, understanding how different forms of play contribute to cognitive development has become a central concern for educators and researchers. This study aims to examine the longitudinal relationship between structured and unstructured play activities and the development of creative problem-solving skills among children aged 4 to 7 years. A mixed-method longitudinal design was employed over a three-year period, involving 120 children from five early childhood education centers. Quantitative data were collected through standardized creativity and problem-solving assessments, while qualitative observations and teacher interviews provided contextual insights into behavioral and cognitive changes. Results revealed that children consistently engaged in imaginative and cooperative play demonstrated significantly higher gains in fluency, flexibility, and originality in problem-solving tasks. The findings also indicate that teacher-facilitated play environments amplify these developmental effects by promoting autonomy and social interaction. The study concludes that play is not merely a recreational activity but a critical pedagogical tool that nurtures creative cognition and adaptive problem-solving in early learning contexts.